Customized feeding plate for nutritional and respiratory support in an infant with Pierre Robin sequence and cleft palate complicated by severe respiratory infections: A case report - Jayanti, Claudia NR.; Anugerah, Evelyn; Soewondo, Willyanti; Pasha, Asep K.; Puratmaja, Galuhafiar (Narra Sains Indonesia, 2025)
Pierre Robin sequence (PRS) is a congenital condition characterized by micrognathia, glossoptosis, and airway obstruction, often accompanied by cleft palate. Feeding difficulties and respiratory compromise pose significant challenges in early management. While feeding plates are commonly used to improve feeding and airway stability, their application in infants with severe respiratory infections remains underreported. The aim of this study was to describe the challenges of impression-taking and feeding plate fabrication in an infant with PRS complicated by multiple congenital anomalies and severe respiratory complications, including bilateral pneumonia. A 23-day-old male infant was referred to the pediatric dentistry department of Pandega General Hospital, Pangandaran, Indonesia, with the chief complaints of feeding difficulties, recurrent choking episodes, and respiratory distress. The patient was diagnosed with PRS with a cleft palate, complicated by congenital tuberculosis and bilateral pneumonia, exacerbating respiratory compromise. Given the patient's fragile condition, impression-taking was performed with strict airway precautions, including lateral positioning, continuous oxygen monitoring, and suction readiness. High-viscosity alginate and a perforated stock tray were used to minimize aspiration risk. Two clinicians ensured airway security throughout the procedure. A customized acrylic feeding plate was fabricated with a palatal extension to prevent nasal regurgitation and a contoured surface to aid tongue positioning. The plate was polished for comfort, adjusted for retention, and fitted to accommodate maxillary growth, ensuring safe and effective feeding support. Within one month, the infant’s weight increased from 2,200 g to 3,100 g, choking episodes significantly decreased, and a transition from orogastric tube to bottle feeding was achieved. In conclusion, this case highlights the feasibility and benefits of feeding plate adaptation in PRS management, even in the presence of severe respiratory infections. A non-invasive approach using a feeding plate can serve as an initial intervention before surgical correction, particularly in fragile neonates.